José Cecilio del Valle y Jeremy Bentham: coincidencias de pensamiento - Pérez Zumbado, Danilo (2018)
The paper set up the relation between Jose Cecilio del Valle and Jeremy Bentham concerning the ideas of mechanicism and the economic man during the period of the independence of Guatemala Reign form Spain -end of XVIII and beginning of XIX centuries-. There is too a short characterization of the historical and intellectual context of each one of them, in particular, the social class, education and labour.